23.20: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/23.20#Ex1 23.20#Ex1] || [[Item:Q7374|<math>x_{3} = m^{2}-x_{1}-x_{2}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>x_{3} = m^{2}-x_{1}-x_{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">x[3] = (m)^(2)- x[1]- x[2]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[x, 3] == (m)^(2)- Subscript[x, 1]- Subscript[x, 2]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/23.20#Ex1 23.20#Ex1] || <math qid="Q7374">x_{3} = m^{2}-x_{1}-x_{2}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>x_{3} = m^{2}-x_{1}-x_{2}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">x[3] = (m)^(2)- x[1]- x[2]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[x, 3] == (m)^(2)- Subscript[x, 1]- Subscript[x, 2]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/23.20#Ex2 23.20#Ex2] || [[Item:Q7375|<math>y_{3} = -m(x_{3}-x_{1})-y_{1}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>y_{3} = -m(x_{3}-x_{1})-y_{1}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">y[3] = - m*(x[3]- x[1])- y[1]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[y, 3] == - m*(Subscript[x, 3]- Subscript[x, 1])- Subscript[y, 1]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/23.20#Ex2 23.20#Ex2] || <math qid="Q7375">y_{3} = -m(x_{3}-x_{1})-y_{1}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>y_{3} = -m(x_{3}-x_{1})-y_{1}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">y[3] = - m*(x[3]- x[1])- y[1]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[y, 3] == - m*(Subscript[x, 3]- Subscript[x, 1])- Subscript[y, 1]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/23.20.E5 23.20.E5] || [[Item:Q7377|<math>v^{8}(1+u^{8}) = 4u^{4}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>v^{8}(1+u^{8}) = 4u^{4}</syntaxhighlight> || <math>p = 2</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(v)^(8)*(1 + (u)^(8)) = 4*(u)^(4)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(v)^(8)*(1 + (u)^(8)) == 4*(u)^(4)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/23.20.E5 23.20.E5] || <math qid="Q7377">v^{8}(1+u^{8}) = 4u^{4}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>v^{8}(1+u^{8}) = 4u^{4}</syntaxhighlight> || <math>p = 2</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(v)^(8)*(1 + (u)^(8)) = 4*(u)^(4)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(v)^(8)*(1 + (u)^(8)) == 4*(u)^(4)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/23.20.E6 23.20.E6] || [[Item:Q7378|<math>u^{4}-v^{4}+2uv(1-u^{2}v^{2}) = 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>u^{4}-v^{4}+2uv(1-u^{2}v^{2}) = 0</syntaxhighlight> || <math>p = 3</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(u)^(4)- (v)^(4)+ 2*u*v*(1 - (u)^(2)* (v)^(2)) = 0</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(u)^(4)- (v)^(4)+ 2*u*v*(1 - (u)^(2)* (v)^(2)) == 0</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/23.20.E6 23.20.E6] || <math qid="Q7378">u^{4}-v^{4}+2uv(1-u^{2}v^{2}) = 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>u^{4}-v^{4}+2uv(1-u^{2}v^{2}) = 0</syntaxhighlight> || <math>p = 3</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(u)^(4)- (v)^(4)+ 2*u*v*(1 - (u)^(2)* (v)^(2)) = 0</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(u)^(4)- (v)^(4)+ 2*u*v*(1 - (u)^(2)* (v)^(2)) == 0</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/23.20.E7 23.20.E7] || [[Item:Q7379|<math>u^{6}-v^{6}+5u^{2}v^{2}(u^{2}-v^{2})+4uv(1-u^{4}v^{4}) = 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>u^{6}-v^{6}+5u^{2}v^{2}(u^{2}-v^{2})+4uv(1-u^{4}v^{4}) = 0</syntaxhighlight> || <math>p = 5</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(u)^(6)- (v)^(6)+ 5*(u)^(2)* (v)^(2)*((u)^(2)- (v)^(2))+ 4*u*v*(1 - (u)^(4)* (v)^(4)) = 0</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(u)^(6)- (v)^(6)+ 5*(u)^(2)* (v)^(2)*((u)^(2)- (v)^(2))+ 4*u*v*(1 - (u)^(4)* (v)^(4)) == 0</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/23.20.E7 23.20.E7] || <math qid="Q7379">u^{6}-v^{6}+5u^{2}v^{2}(u^{2}-v^{2})+4uv(1-u^{4}v^{4}) = 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>u^{6}-v^{6}+5u^{2}v^{2}(u^{2}-v^{2})+4uv(1-u^{4}v^{4}) = 0</syntaxhighlight> || <math>p = 5</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(u)^(6)- (v)^(6)+ 5*(u)^(2)* (v)^(2)*((u)^(2)- (v)^(2))+ 4*u*v*(1 - (u)^(4)* (v)^(4)) = 0</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(u)^(6)- (v)^(6)+ 5*(u)^(2)* (v)^(2)*((u)^(2)- (v)^(2))+ 4*u*v*(1 - (u)^(4)* (v)^(4)) == 0</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/23.20.E8 23.20.E8] || [[Item:Q7380|<math>(1-u^{8})(1-v^{8}) = (1-uv)^{8}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>(1-u^{8})(1-v^{8}) = (1-uv)^{8}</syntaxhighlight> || <math>p = 7</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(1 - (u)^(8))*(1 - (v)^(8)) = (1 - u*v)^(8)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(1 - (u)^(8))*(1 - (v)^(8)) == (1 - u*v)^(8)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/23.20.E8 23.20.E8] || <math qid="Q7380">(1-u^{8})(1-v^{8}) = (1-uv)^{8}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>(1-u^{8})(1-v^{8}) = (1-uv)^{8}</syntaxhighlight> || <math>p = 7</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(1 - (u)^(8))*(1 - (v)^(8)) = (1 - u*v)^(8)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(1 - (u)^(8))*(1 - (v)^(8)) == (1 - u*v)^(8)</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|}
|}
</div>
</div>

Latest revision as of 12:01, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
23.20#Ex1 x 3 = m 2 - x 1 - x 2 subscript 𝑥 3 superscript 𝑚 2 subscript 𝑥 1 subscript 𝑥 2 {\displaystyle{\displaystyle x_{3}=m^{2}-x_{1}-x_{2}}}
x_{3} = m^{2}-x_{1}-x_{2}

x[3] = (m)^(2)- x[1]- x[2]
Subscript[x, 3] == (m)^(2)- Subscript[x, 1]- Subscript[x, 2]
Skipped - no semantic math Skipped - no semantic math - -
23.20#Ex2 y 3 = - m ( x 3 - x 1 ) - y 1 subscript 𝑦 3 𝑚 subscript 𝑥 3 subscript 𝑥 1 subscript 𝑦 1 {\displaystyle{\displaystyle y_{3}=-m(x_{3}-x_{1})-y_{1}}}
y_{3} = -m(x_{3}-x_{1})-y_{1}

y[3] = - m*(x[3]- x[1])- y[1]
Subscript[y, 3] == - m*(Subscript[x, 3]- Subscript[x, 1])- Subscript[y, 1]
Skipped - no semantic math Skipped - no semantic math - -
23.20.E5 v 8 ( 1 + u 8 ) = 4 u 4 superscript 𝑣 8 1 superscript 𝑢 8 4 superscript 𝑢 4 {\displaystyle{\displaystyle v^{8}(1+u^{8})=4u^{4}}}
v^{8}(1+u^{8}) = 4u^{4}
p = 2 𝑝 2 {\displaystyle{\displaystyle p=2}}
(v)^(8)*(1 + (u)^(8)) = 4*(u)^(4)
(v)^(8)*(1 + (u)^(8)) == 4*(u)^(4)
Skipped - no semantic math Skipped - no semantic math - -
23.20.E6 u 4 - v 4 + 2 u v ( 1 - u 2 v 2 ) = 0 superscript 𝑢 4 superscript 𝑣 4 2 𝑢 𝑣 1 superscript 𝑢 2 superscript 𝑣 2 0 {\displaystyle{\displaystyle u^{4}-v^{4}+2uv(1-u^{2}v^{2})=0}}
u^{4}-v^{4}+2uv(1-u^{2}v^{2}) = 0
p = 3 𝑝 3 {\displaystyle{\displaystyle p=3}}
(u)^(4)- (v)^(4)+ 2*u*v*(1 - (u)^(2)* (v)^(2)) = 0
(u)^(4)- (v)^(4)+ 2*u*v*(1 - (u)^(2)* (v)^(2)) == 0
Skipped - no semantic math Skipped - no semantic math - -
23.20.E7 u 6 - v 6 + 5 u 2 v 2 ( u 2 - v 2 ) + 4 u v ( 1 - u 4 v 4 ) = 0 superscript 𝑢 6 superscript 𝑣 6 5 superscript 𝑢 2 superscript 𝑣 2 superscript 𝑢 2 superscript 𝑣 2 4 𝑢 𝑣 1 superscript 𝑢 4 superscript 𝑣 4 0 {\displaystyle{\displaystyle u^{6}-v^{6}+5u^{2}v^{2}(u^{2}-v^{2})+4uv(1-u^{4}v% ^{4})=0}}
u^{6}-v^{6}+5u^{2}v^{2}(u^{2}-v^{2})+4uv(1-u^{4}v^{4}) = 0
p = 5 𝑝 5 {\displaystyle{\displaystyle p=5}}
(u)^(6)- (v)^(6)+ 5*(u)^(2)* (v)^(2)*((u)^(2)- (v)^(2))+ 4*u*v*(1 - (u)^(4)* (v)^(4)) = 0
(u)^(6)- (v)^(6)+ 5*(u)^(2)* (v)^(2)*((u)^(2)- (v)^(2))+ 4*u*v*(1 - (u)^(4)* (v)^(4)) == 0
Skipped - no semantic math Skipped - no semantic math - -
23.20.E8 ( 1 - u 8 ) ( 1 - v 8 ) = ( 1 - u v ) 8 1 superscript 𝑢 8 1 superscript 𝑣 8 superscript 1 𝑢 𝑣 8 {\displaystyle{\displaystyle(1-u^{8})(1-v^{8})=(1-uv)^{8}}}
(1-u^{8})(1-v^{8}) = (1-uv)^{8}
p = 7 𝑝 7 {\displaystyle{\displaystyle p=7}}
(1 - (u)^(8))*(1 - (v)^(8)) = (1 - u*v)^(8)
(1 - (u)^(8))*(1 - (v)^(8)) == (1 - u*v)^(8)
Skipped - no semantic math Skipped - no semantic math - -